Life Cycle of the Cardiac Voltage-Gated Sodium Channel NaV1.5 - Dong, Caijuan; Wang, Ya; Ma, Aiqun; Wang, Tingzhong (Frontiers in Physiology, 2020)
Cardiac voltage-gated sodium channel NaV1.5, encoded by SCN5A, is crucial for the upstroke of action potential and excitation of cardiomyocytes. NaV1.5 undergoes complex processes before it reaches the target membrane microdomains and performs normal functions. A variety of protein partners are needed to achieve the balance between SCN5A transcription and mRNA decay, endoplasmic reticulum retention and export, Golgi apparatus retention and export, selective anchoring and degradation, activation, and inactivation of sodium currents. Subtle alterations can impair NaV1.5 in terms of expression or function, eventually leading to NaV1.5-associated diseases such as lethal arrhythmias and cardiomyopathy.